Mesencephalic Astrocyte-Derived Neurotrophic Factor (MANF) Is Highly Expressed in Mouse Tissues With Metabolic Function - Danilova, Tatiana; Galli, Emilia; Pakarinen, Emmi; Palm, Erik; Lindholm, Päivi; Saarma, Mart; Lindahl, Maria (Frontiers in Endocrinology, 2019)
Mesencephalic astrocyte-derived neurotrophic factor (MANF) and cerebral dopamine neurotrophic factor (CDNF) form a family of atypical growth factors discovered for their neuroprotective properties in the central nervous system (CNS) in animal models of neurodegenerative diseases. Although their mechanism of protective action still remains unclear, it has been suggested that both MANF and CDNF promote cell survival through regulating the unfolded protein response (UPR), thereby relieving endoplasmic reticulum (ER) stress. Recent studies identified MANF for its emerging roles in metabolic function, inflammation and pancreatic -cells. We have found that MANF deletion from the pancreas and -cells leads to postnatal depletion of -cells and diabetes. Moreover, global MANF-deficiency in mice results in severe diabetes-independent growth retardation. As the expression pattern of MANF in mouse tissues has not been extensively studied, we set out to thoroughly investigate MANF expression in embryonic and adult mice using immunohistochemistry, histochemical X-gal staining, enzyme-linked immunosorbent assay (ELISA) and quantitative reverse transcription PCR (RT-qPCR). We found that MANF is highly expressed in brain neurons regulating energy homeostasis and appetite, as well as in hypothalamic nuclei producing hormones and neuropeptides important for different body functions. Strong expression of MANF was also observed in peripheral mouse tissues and cells with high secretory and metabolic function. These include pituitary gland and interestingly we found that the anterior pituitary gland is smaller in MANF-deficient mice compared to wild-type mice. Consequently, we found reduction in the number of growth hormone- and prolactin-producing cells. This combined with increased expression of UPR genes, reduced number of proliferating cells in the anterior pituitary and dysregulated expression of pituitary hormones might contribute to the severe growth defect seen in the MANF knockout mice. Moreover, in this study we compared MANF and CDNF levels in mouse tissues. Unlike MANF, CDNF protein levels are generally lower in mouse tissues, and the highest levels of CDNF was observed in the tissues with high-energy demands and oxidative roles, including heart, muscle, testis, and brown adipose tissue.